Quantifying cilia beat frequency using high‐speed video microscopy: Assessing frame rate requirements when imaging different ciliated tissues. Issue 11 (8th June 2022) - Scopulovic, Luke; Francis, Deanne; Pandzic, Elvis; Francis, Richard
Abstract: Motile cilia are found in numerous locations throughout our body and play a critical role in various physiological processes. The most commonly used method to assess cilia motility is to quantify cilia beat frequency (CBF) via video microscopy. However, a large heterogeneity exists within published literature regarding the framerate used to image cilia motility for calculating CBF. The aim of this study was to determine the optimal frame rate required to image cilia motility for CBF assessment, and if the Nyquist theorem may be used to set this rate. One‐second movies of cilia were collected at >600 fps from mouse airways and ependyma at room‐temperature or 37°C. Movies were then down‐sampled to 30–300 fps. CBF was quantified for identical cilia at different framerates by either manual counting or automated MATLAB script. Airway CBF was significantly impaired in 30 fps movies, while ependymal CBF was significantly impaired in both 60 and 30 fps movies. Pairwise comparison showed that video framerate should be at least 150 fps to accurately measure CBF, with minimal improvement in CBF accuracy in movies >150 fps. The automated script was also found to be less accurate for measuring CBF in lower fps movies than manual counting, however, this difference disappeared in higher framerate movies (>150 fps). In conclusion, our data suggest the Nyquist theorem is unreliable for setting sampling rate for CBF measurement. Instead, sampling rate should be 3–4 times faster than CBF for accurate CBF assessment. Especially if CBF calculation is to be automated. Abstract : The aim of this study was to determine the optimal frame rate required to image cilia motility for cilia beat frequency assessment, and if the Nyquist theorem may be used to set this rate. our data suggests the Nyquist theorem is unreliable for setting imaging sampling rate for cilia beat frequency measurement. Instead, sampling rate should be 3–4 times faster than cilia beat frequency for accurate CBF assessment.